Georgia in the context of the European educational area - Manana Darchashvili (Ömer Gökhan Ulum, 2021)
In Georgia, the issue of education has always been a priority for the government of all times, with a focus on further development. In 2005, when Georgia joined the Bologna Process, significant reforms were made in the higher education system. Higher education programs are described in the European Credit Transfer System. Accordingly, the diploma supplement is approved following the rules developed in Europe. The paper examines the compatibility of the country's education system with the law, according to which the existing higher education institutions must comply with both internal and external quality assurance mechanisms. The external quality assurance system of Georgia consists of authorization and program accreditation, and external quality assurance is provided by LEPL National Center for Education Quality Development. The paper presents the ways and means of Georgia's firm establishment in the European educational space and the contribution of the National Center for Quality Development in Education so that the quality of education received in Georgia fully meets national and international requirements.